Aramaic calque in Hebrew: של הארמית בעברית (calque) בבואה - Kutscher, E. Y.
י׳ קוטשר; English summary; u.a. zu DSS IQS 2, 9 אחז אבית = ‘to intercede’ über Syriac אחד אבותא aus akk. abbūtu ṣabātu/aḫāzu.